Effect of COVID-19 on the Role of Renin Enzyme and ACE2 and Hormones in PCOS Females - Shaimaa Emad Ali; Fayhaa M. Khaleel (مجلة بغداد للعلوم)
Polycystic ovary syndrome (PCOS) is the most endocrine problem in women of regenerative age. PCOS women typically belong to an age and sex group which is at higher risk for severe coronavirus disease (COVID-19). COVID-19 targets cells through angiotensin-converting enzyme 2 (ACE2) receptor presents on cells in veins, lungs, heart, digestion tracts, and kidneys. Renin-Angiotensin System (RAS) over activity has likewise been described in metabolic disorders; type 2 diabetes mellitus (T2DM), and conditions shared by women with polycystic ovary condition. The point of this study is to know the job of renin and ACE2 in PCOS and coronavirus and its relationship with hormones and other metabolic parameters related. The study groups consist of 120 sample subjects consisting of 80 PCOS-women divided into two groups: - (40 PCOS-women infected with COVID-19 and 40 PCOS-women non-infected with COVID-19) and 40 healthy-women divided into two groups: - 20 women-COVID-19 infected, and 20 women non-COVID-19 infected, ranging in age from 15–40 years old.  Renin and ACE2, FBS, lipid profile, level of insulin, HOMA IR, FSH, LH, and testosterone, were measured for all participants. There was an increase in the levels of renin, ACE2, insulin, HOMA-IR, LH, LH / FSH ratio, and testosterone, except HDL and FSH were low when comparing PCOS patients groups with healthy groups. There was a decrease in renin and ACE2 in PCOS women infected with COVID-19 compared with PCOS women non-infection with COVID-19. Infection of COVID-19 and low ACE2 levels lead to respiratory damage and problem in reproductive in PCOS patients. Also, at the same time ACE2 high level in PCOS makes them more risk for coronavirus and is not involved in the cause of PCOS, however renin enzyme may be affected by BMI associated with PCOS.